A new record for Limnobatodes paradoxus Hussey, 1925 from Guyana (Hemiptera: Heteroptera: Hydrometridae: Limnobatodinae) - Cianferoni, Fabio (Zootaxa, 2014)
Limnobatodes paradoxus Hussey, 1925 is a primitive hydrometrid, described from a single female specimen collected in 1923 at Tela, Honduras (Hussey 1925). Following the original description, very few records of this species have been reported in literature, and locality indications are not detailed: Brazil (Cobben 1968), Peru (Andersen 1977), and French Guiana (Polhemus & Polhemus 1995). Andersen (1977, 1982) quoted “British Honduras” [= Belize] instead of Honduras, and this mistake was subsequently repeated by Schuh and Slater (1995) (see Moreira, 2014). This taxon was not listed by Heckman (2011) in his monograph on the Heteroptera of South America. Excellent illustrations of this species, in comparison with those of other Heteroptera, have been provided by several authors (cf. Hussey 1925; Cobben 1968, 1978; Andersen 1977, 1982). Nothing is known about the habitat and life history of Limnobatodes paradoxus (Andersen 1977; Polhemus & Polhemus 1995).